2021
DOI: 10.2196/27122
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Oncologists’ Perceptions of Adopting an Artificial Intelligence–Assisted Contouring Technology: Model Development and Questionnaire Study

Abstract: Background An artificial intelligence (AI)–assisted contouring system benefits radiation oncologists by saving time and improving treatment accuracy. Yet, there is much hope and fear surrounding such technologies, and this fear can manifest as resistance from health care professionals, which can lead to the failure of AI projects. Objective The objective of this study was to develop and test a model for investigating the factors that drive radiation onc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 49 publications
2
40
0
Order By: Relevance
“…In our questionnaire, few agreed that AI is more accurate than physicians (15% agreement), but these objectors seemed to be more confident in AI's efficiency with 52% agreeing that "clinical AI is more efficient than physicians" (Figure 3). Four studies used structural equation modeling to identify determinants of adoption intention for clinical AI among healthcare providers and medical students (38, [65][66][67]. Perceived usefulness, the experience of using mHealth, subjective norms, and social influence had a positive effect on adoption intention, while perceived risk had the opposite effect.…”
Section: Attitude and Acceptability Of Clinical Artificial Intelligencementioning
confidence: 99%
“…In our questionnaire, few agreed that AI is more accurate than physicians (15% agreement), but these objectors seemed to be more confident in AI's efficiency with 52% agreeing that "clinical AI is more efficient than physicians" (Figure 3). Four studies used structural equation modeling to identify determinants of adoption intention for clinical AI among healthcare providers and medical students (38, [65][66][67]. Perceived usefulness, the experience of using mHealth, subjective norms, and social influence had a positive effect on adoption intention, while perceived risk had the opposite effect.…”
Section: Attitude and Acceptability Of Clinical Artificial Intelligencementioning
confidence: 99%
“…Currently, it functions best as an adjunct to manual delineation. While it can assist in reducing manual contouring time, 34 the process of organ and tumor sketching remains onerous for doctors. In addition to the hurdles of precise automatic segmentation, dataset collection and acquisition is also problematic as fully supervised learning and model efficiency is dependent on high‐quality datasets.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Nikolov et al [20] demonstrated a novel 3D U-Net architecture that could achieve expert-level performance while delineating 21 distinct head-and-neck target commonly segmented in clinical practice. While AI-assisted contouring can effectively empower clinicians beyond their current practices [35], there is a high cost associated to false positives and negatives in this domain. In addition, to support effective AI-approaches, large datasets are required and the limited availability of those large datasets impacts the scalability of applying AI to contouring.…”
Section: Background and Related Work 21 Contour Delineation In Radiot...mentioning
confidence: 99%
“…Contour delineation is a critical step in RT workflow where practicing oncologists identify and outline malignant tumors and/or healthy organs from a stack of medical images. Inaccurate contouring could lead to systematic errors throughout the entire treatment course, leading to either miss the malignant tumors, or over-treat the healthy tissues [35]. From the patient's side, poor contouring could cause increased risks of toxicity, tumor recurrence and death.…”
Section: Introductionmentioning
confidence: 99%